2005
DOI: 10.1529/biophysj.104.048876
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size Distribution in DMPC Vesicles Solutions Undergoing Different Sonication Times

Abstract: Size distribution of dimyristoylphosphatidylcholine liposome suspensions was investigated by dynamic-light scattering (DLS) as a function of the sonication time (t(s)). Cumulant expansion (second- and third-order) and regularized Laplace inversion (CONTIN) of dynamic single-angle laser light-scattering data were performed. With both methods, the intensity-weighted mean hydrodynamic radius r(I) depended on the investigated lengthscale. The number-weighted mean hydrodynamic radius (r(N)), obtained from CONTIN by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(85 citation statements)
references
References 19 publications
2
82
0
1
Order By: Relevance
“…Small unilamellar vesicles (SUVs) were obtained by sonicating the lipid suspension for 15 minutes with a bath-type sonicator (Transsonic 460/H from Elma) operated under a power of 170 W. This method gave a particle size distribution between 25 nm and 30 nm. [30,31] The solution of lipid vesicles was then incubated with the clean diamond samples for 2 hours at 60 8C to form an intact bilayer on the surface, after which excess vesicles in the bulk were removed by rinsing with de-ionized water. 0.5% and 0.0025% of Rho-PE was mixed with the lipid mixture for FRAP and FCS measurements, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Small unilamellar vesicles (SUVs) were obtained by sonicating the lipid suspension for 15 minutes with a bath-type sonicator (Transsonic 460/H from Elma) operated under a power of 170 W. This method gave a particle size distribution between 25 nm and 30 nm. [30,31] The solution of lipid vesicles was then incubated with the clean diamond samples for 2 hours at 60 8C to form an intact bilayer on the surface, after which excess vesicles in the bulk were removed by rinsing with de-ionized water. 0.5% and 0.0025% of Rho-PE was mixed with the lipid mixture for FRAP and FCS measurements, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4][5][6] For polymeric aggregates, the effect of sonication has been scarcely and fragmentally studied. [2,[5][6] Kataoka and coworkers [2] found that poly(ethylene oxide)-block-poly(amino acid) block copolymers, after dialysis from organic solvent to water, formed large associates of polymeric micelles, which could be separated into well-dispersed micelles by the aid of sonication.…”
Section: Introductionmentioning
confidence: 99%
“…Vesicles were assembled by stirring the lipid solution and then small unilamellar vesicles were prepared by mild sonication using a bath-type sonicator. The size of vesicles is estimated to be about 10-50 nm from the reported experimental results using similar conditions [28]. To accelerate the vesicle rupture on the substrate surface, the lipid solution temperature was kept at 60…”
Section: Methodsmentioning
confidence: 99%